VD_FINDINFO Jug / 2013 / 53 vom 6. März 2013 - VD Tribunal cantonal (2013)
ACQUITTEMENT, INDEMNITÉEN GÉNÉRAL, TORT MORAL, INDEMNITÉ POUR DÉTENTION, DÉTENTION INJUSTIFIÉE | 429 al. 1 let. a CPP (CH), 429 al. 1 let. c CPP (CH), 429 al. 2 CPP (CH), 429 CPP (CH), 430 CPP (CH)